Enhancing Coral Settlement Through a Novel Larval Feeding Protocol - Colleen Rodd; Colleen Rodd; Steve Whalan; Steve Whalan; Craig Humphrey; Peter L. Harrison; Peter L. Harrison (Frontiers in Marine Science, 2022)
Intensifying anthropogenic stressors have contributed to declines in reef-building corals in many regions. These disturbances result in reduced live coral cover, impacting key population-level processes such as coral larval settlement and recruitment that are essential for reef recovery. Reef restoration efforts that rely on enhanced larval supply provide a pathway for the recovery of degraded reefs. However, corals at very early life stages experience high post-settlement mortality bottlenecks, which impede stock-recruitment processes. Overcoming these bottlenecks is a high priority goal in coral restoration. Some coral larvae are known to be capable of gaining exogenous nutrients. Therefore, we hypothesised that the capacity to access exogenous nutrients may confer advantages to larval survival, settlement and post-settlement success. The present study aimed to quantify the effect of larval feeding on coral larvae settlement and early post-settlement survival. We completed an ex-situ experiment using aposymbiotic larvae of two broadcast spawning reef-building coral species - Acropora tenuis and Acropora millepora. Larvae were randomly assigned to either fed or unfed treatment groups for each species. Fed larvae received homogenised Artemia once a day, for three days. Results show that for both species, feeding significantly increased larval settlement. Feeding A. millepora larvae more than doubled mean settlement (13.0 ± 1.17 SE vs 31.4 ± 2.88 SE; p <0.001). Similarly, feeding A. tenuis larvae increased mean settlement from 18.2 ( ± 1.85 SE) to 29.9 ( ± 2.22 SE; p <0.001). Larval feeding had an immediate positive effect on spat survival, such that A. millepora and A. tenuis spat from fed treatments had increased survival three days post-settlement (89.5% ± 3.75 SE vs 70.6% ± 2.59 SE, p <0.001; 88.8% ± 2.21 SE vs 71.4% ± 3.80 SE, p <0.001, respectively). Therefore, enhancing settlement and early post-settlement survival by feeding larvae homogenised Artemia has the potential to improve the effectiveness of larval rearing protocols and coral restoration efforts.